Modern parenting in the digital world - Berezetskaya, Mariya I. (Journal of the Belarusian State University. Sociology, 2020)
The paper is concerned with sociological analysis of parenting in modern society. The development of computer technology, the widespread dissemination of the Internet, the advent of smartphones and mobile applications have significantly changed strategies of parenting behavior. This article discusses the features of the parental behavior in a digital environment and their use of informational technology. Special attention is paid to the description of websites, online forums, social networks, mobile applications as platforms for interaction between parents and with their children. Specialized websites, forums, social networks combine information and entertainment functions: on these sites parents not only share tips and tricks on children’s bringing up, but also find like-minded friends. Mobile applications and messengers allow modern parents to be in touch with their children and to have information about their location being at a great distance from them and without serious material costs. The phenomenon of parents-bloggers and children-bloggers, as well as the problem of security and confidentiality of data on the Internet, is carefully analyzed in this article. In modern parental behavior there is a tendency to demonstrate parenting in social networks. For example, the number of parents-bloggers and children-bloggers grows, blogging become the instrument for earning money. The article contains the results of an author’s study of the thematic focus of parent blogs on Instagram.